O que dizem os intérpretes de Libras do sudeste goiano sobre formação e atuação - Jordão, Uiara Vaz (Universidade Federal de São Carlos, 2013)
This paper try to analyze the characteristics of training the Goiano Southeast Libras interpreters, about deafness knowledge / Libras and check the limits and potentials observed by them for their work with deaf students from the elementary school and / or high school. In this perspective, this research is an exploratory study of the Libras interpreter s condition in southeastern state of Goiás, realized from documental analyze and mix questionnaire, which try to find answers to the following question: what is the training of Libras interpreters in Southeast Goiano and what are the limits and potentials observed by them for their role as interpreters from this training? This paper talk about eleven participants who acted in Basic Education in state schools. The analyzes obtained about what the performers say about their training show us a lot of important aspects that interfere with their professional activities, such as, absence of training covering concepts about deaf education and the role of Libras interpreter; learning based in isolated signals, in short courses whose focus is to teach the language to be user; professionals working in a school with deaf students as if they were experts in the language, and validation of them performance based on hours of study and a certification acquired (or not) after being approved in a test performed on an organ of the state government.
Keywords: Educação Especial; Intérprete de Libras; Formação profissional; Atuação profissional; Libras interpreter; Formation; Performance; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL